Significance of Oral Literature – A Scrutiny with Reference to Son of the Thundercloud by Easterine Kire. (International Journal of Food and Nutritional Sciences, 2022)
Oral literature plays a key role in the field of literature. Stories act as a medium topass on the wisdom of one’s culture from generation to generation and from countryto country. It is filled with both acknowledged and mysterious history. It can beconsidered as a tapestry weaved by stories, myths, beliefs and legends. And so, it isnecessary to support oral literature in every culture. Nagaland is a state in India whichis rich in culture and tradition. Oral literature existed in every culture as water to earthonce. But, modernisation generated a famine of stories and story tellers swallowing upthe wisdom of oral literature. This paper emphasises the prominence of oral literaturein every culture with reference to the Novel Son of the Thundercloud.